Digital Storytelling in Cultural Tourism: A Sustainable Communication Approach at the Lasem Heritage Foundation - Intan Putri Cahyani; Puri Bestari Mardani; Yuliani Widianingsih (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
Responsible cultural tourism requires a sustainable approach that includes preserving cultural values while promoting economic and environmental sustainability. This study examines why the Lasem Heritage Foundation chose digital storytelling as a form of sustainable communication for managing cultural tourism and how it aligns with sustainable communication principles. Using a case study approach and qualitative methods, data were collected through interviews, observation, and literature review. Findings indicate that digital storytelling is an effective approach to managing cultural tourism for the Lasem Heritage Foundation, as it provides lasting impact and message amplification. Their Instagram and Website with "Kesengsem Lasem" as tourism branding have helped the foundation communicate and amplify their cultural values to the public and promote sustainable tourism practices to wider audiences. Furthermore, The foundation's use of digital storytelling as a sustainable communication approach in managing cultural tourism effectively conveys lasting messages and helps reinforce the cultural values and environmental sustainability of the destination. These include (1) Ecological Trust in their website articles, (2) ecological access in their Social Business Programs, (3) ecological disclosures in the use of Instagram and Website as the leading platform of digital storytelling & communication tools with all stakeholders, and (4) ecological dialogues in their preservation class, series of learning clinic, and a particular program called to travel for all. Future research should expand the number of informants and consider additional data collection methods such as focus group discussions and content analysis of digital platforms.